Impact of Spacing and Orientation on the Scar Threshold With a High-Density Grid Catheter. (September 2019) - Takigawa, Masateru; Relan, Jatin; Kitamura, Takeshi; Martin, Claire A.; Kim, Steven; Martin, Ruairidh; Cheniti, Ghassen; Vlachos, Konstantinos; Massoullié, Grégoire; Frontera, Antonio; Thompson, Nathaniel; Wolf, Michael; et al.
Abstract : Background: Multipolar catheters are increasingly used for high-density mapping. However, the threshold to define scar areas has not been well described for each configuration. We sought to elucidate the impact of bipolar spacing and orientation on the optimal threshold to match magnetic resonance imaging-defined scar. Method: The HD-Grid catheter uniquely allows for different spatially stable bipolar configurations to be tested. We analyzed the electrograms with settings of HD-16 (3 mm spacing in both along and across bipoles) and HD-32 (1 mm spacing in along bipoles and 3 mm spacing in across bipoles) and determined the optimal cutoff for scar detection in 6 infarcted sheep. Results: From 456 total acquisition sites (mean 76±12 per case), 14 750 points with the HD-16 and 32286 points with the HD-32 configuration for bipolar electrograms were analyzed. For bipolar voltages, the optimal cutoff value to detect the magnetic resonance imaging-defined scar based on the Youden's Index, and the area under the receiver operating characteristic curve (AUROC) differed depending on the spacing and orientation of bipoles; across 0.84 mV (AUROC, 0.920; 95% CI, 0.911–0.928), along 0.76 mV (AUROC, 0.903; 95% CI, 0.893–0.912), north-east direction 0.95 mV (AUROC, 0.923; 95% CI, 0.913–0.932), and south-east direction, 0.87 mV (AUROC, 0.906; 95% CI, 0.895–0.917) in HD-16; and across 0.83 mV (AUROC, 0.917; 95% CI, 0.911–0.924), along 0.46 mV (AUROC, 0.890; 95% CI, 0.883–0.897), north-east direction 0.89 mV (AUROC, 0.923; 95% CI, 0.917–0.929), and south-east direction 0.83 mV (AUROC, 0.913; 95% CI, 0.906–0.920) in HD-32. Significant differences in AUROC were seen between HD-16 along versus across ( P =0.002), HD-16 north-east direction versus south-east direction ( P =0.01), HD-32 north-east direction versus south-east direction ( P <0.0001), and HD-16 along versus HD-32 along ( P =0.006). The AUROC was significantly larger ( P <0.01) when only the best points on each given site were selected for analysis, compared with when all points were used. Conclusions: Spacing and orientation of bipoles impacts the accuracy of scar detection. Optimal threshold specific to each bipolar configuration should be determined. Selecting one best voltage point among multiple points projected on the same surface is also critical on the Ensite-system to increase the accuracy of scar-mapping. Abstract : Supplemental Digital Content is available in the text.